A REVIEW ON MULTISCALE TEXTURE FEATURES USING STEERABLE PYRAMIDS (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
As a result of recent advancements in digital storage technology, it is now possible to create large and extensive databases of digital imagery. These collections may contain millions of images and terabytes of data. For users to make the most of these databases effective, efficient methods of searching must be devised. Having a computer do the indexing based on a CBIR scheme attempts to address the shortcomings of human-based indexing. Since a computer can process images at a much higher rate, while never tiring, the manpower issue is solved. In this paper, we will discuss the architecture of CBIR with steerable pyramids and their shortcomings.